Gel casting of sialon ceramics based on water soluble epoxy resin. Issue 9 (November 2015) - Liu, Gang; Attallah, Moataz M.; Loretto, Mike; Herny, Emilie; Jiang, Yun; Button, Tim W.
Abstract: A recently developed gel casting system based on water soluble epoxy resin was successfully applied to sialon ceramics. The solids loading could reach 48.9% without any pH adjustment, and all slurries exhibited shear-thinning behaviour. Flexural strengths of sialon ceramic obtained from 44.5 vol% slurry were 295.2 MPa at room temperature and 281.4 MPa at 700 °C; the microhardness was 16.5 GPa. The net-shape manufacturing of sialon ceramics could benefit from this investigation.